How much time to figure out how to get where? Route planning and subjective stress under time pressure - Paul E. Plonski; Prsni Patel; Kathryn L. Ossenfort; Holly A. Taylor; Tad T. Brunyé; Heather L. Urry (PLoS ONE, 2025)
From a daily commute to military operations in hostile territory and natural disaster responses, people frequently move from place to place. Cognition (e.g., wayfinding) occurs in conjunction with behavior (e.g., locomotion) to facilitate spatial navigation–intentional movement through space. People often use maps to plan routes, which is part of wayfinding. Time pressure is common during navigation, even during route planning, for example from time constraints (e.g., a deadline), waiting periods (e.g., technological problems), or imposed urgency (e.g., someone tells you to hurry up). Route planning requires knowing where to go, determining how to get there, and managing transient stressors that can influence performance. Across cognitive and behavioral domains, time pressure is often conceptualized as a stressor and examined with a single operationalization. As a result, we do not know to what extent time constraints, waiting periods, and imposed urgency independently or interactively a) contribute to the sense of subjective stress, and b) impact spatial performance. Our work addressed these knowledge gaps using a computerized spatial task that centrally involved planning and tracing routes on maps. We describe this new methodology for studying route planning and demonstrate experimental effects of urgency messaging on increased subjective stress and decreased time between map presentation and first click (planning time). When participants took longer to plan or drew longer routes, they reported greater subjective stress. Results carry implications for the design and implementation of time pressure manipulations, route planning in stressful conditions, and mitigating or optimizing stress effects on performance.